A Study of Profile of Children aged 2 months to 5 years admitted with tachypnoea (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Tachypnea can be the presentation of multiple different pathologies.A focused history and physical exam,along with an understanding of the pathophysiology of appropriate disease states,can lead to thorough evaluation and management at the bedside.  Tachypnea may not be present in respiratory illness only, but also in cardiological causes, underlying neurological disorders, metabolic disorders, sepsis, haematological conditions leading to severe anaemia.The aim of this study: The aim of this study is to find out the occurrence and clinical profile of tachypnea in hospitalised children from 2 months to 5 years of age.Study design: The study is designed to be a descriptive  observational study conducted over a period of    year among   children aged 2 months to 5  years admitted at a tertiary care hospital.Out of  846    total admission 145   had tachypnoea. Overall occurrence of tachypnoea was 17.13%Observation: Occurance of tachypnoea among 2 months to 12 months was 24.53% and 13 months to 60 months was 11.13 %,more number of infants were suffering from tachypnoea owing to the infantile respiratory anatomy they have.More deaths were observed in infantile age group.Acute respiratory tract infection (N=107 )( 73.79%)is the most common cause of tachypnea among which, pneumonia was the most common cause of tachypnoea constituting 57 patients (53.27   %) , Severe anaemia with Congestive Cardiac Failure was 2nd most common cause- 8.96% and shock constituted 3rd leading cause of tachypnea with 7.58%, underlying cardiac causes constituted-5. 51  %, underlying neurological causes constituted-4.13%, metabolic causes (DKA) constituted- 1.37%.